Cohesive zone models of single step joint damaged due to the shear crack - Verbist, Maxime Paul Augustin (2020)
Being subject to the horizontal thrust from the carpentry, the Single Step Joint (SSJ) may be damaged due to the shear crack in the tie beam, entailing the collapse of the whole timber truss. In order to prevent this brittle failure mode, the reliability of SSJ design model against the shear crack must be improved by introducing the reducer coefficient k[...], taking into account the Hammock Shape Shear Stress Distribution (HSSSD), parallel to the grain at the heel depth in the tie beam. The HSSSD and reducer coefficient k[...] are significantly influenced by two SSJ geometrical parameters: i) the geometrical proportion between the shear length and heel depth /d/t[...] and ii) the inclination angle a of the front-notch surface. The present study aims at determining the values of k[...] by comparing the numerical results through Finite Element Models (FEM) with the experimental results for several SSJ geometrical configurations tested. To this end, the HSSSD must be assessed through different parameters (e.g. average shear stress r[...]. In order to obtain a realistic curve of the HSSSD, a Cohesive Zone Model has been settled to simulate the shear crack parallel to the grain at the heel depth in the tie beam. The numerical results have shown a strong dependence between the average shear stress r[...] in the tie beam and both SSJ geometrical parameters a and 1,1t5. Furthermore, the reducer coefficient k[...] has been determined as a product of two components: kv,red,¢ and lc[...] rect,uvrd. In addition of meeting both conditions 1 and kv,red,iv/tv 5 1, empirical equations for both components of the reducer coefficient have been proposed in order to enhance the reliability of the SSJ design model against the shear crack.